Unsettling the 'Challenge': ELT Policy Ideology and the New Breach Amongst State-funded Schools in Colombia. Issue 3 (3rd July 2019) - Miranda, Norbella; Valencia Giraldo, Silvia
ABSTRACT: This article examines the ideologies present in Colombian official policy for English language teaching (ELT) and traces the links between governmental planning for state-funded schools and school pedagogical practices. Building on analysis of interviews with policy agents, policymakers' pronouncements, documents and classroom observations, the article contends that instead of working towards educational equity, official policy actions are creating a new breach amongst state-funded schools, that is, between schools that are 'focalised' and others that are not. The national high-stakes exam for school leavers and the strategy of presenting policy goals and outcomes as a constant challenge perpetuate the knowledge-based economy ideology in the policy documents and pose a limit to teachers' and schools' decisions. The paper concludes with a call for a clear analysis of the material contexts of the ELT policy by policy actors at the macro-level and teacher agency that leads to student language learning despite policy constraints.